2022
DOI: 10.1021/jacs.2c01686
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Enantioselective Nucleophilic α-C(sp3)–H Alkenylation of 2-Acyl Imidazoles

Abstract: Merging electrochemistry with asymmetric catalysis promises to provide an environmentally friendly and efficient strategy for the construction of nonracemic chiral molecules. However, in practice, significant challenges arise from the instability or incompatibility of the chiral catalysts under the electrochemical conditions at the interface of electrode and solution. Herein, we report a catalytic asymmetric indirect electrolysis employing the combination of a redox mediator and a chiral-at-rhodium Lewis acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…A catalytic current around 10 μA scale (Fig. 6f ) was detected, similar to the catalytic current observed in the reported Cu-catalyzed 68 , 69 and Rh-catalyzed 70 electrochemical asymmetric syntheses. This observation revealed that the reduced Pd species instantly transfers an electron to 2a to generate intermediate E , which again accepts an electron from the cathode.…”
Section: Resultssupporting
confidence: 86%
“…A catalytic current around 10 μA scale (Fig. 6f ) was detected, similar to the catalytic current observed in the reported Cu-catalyzed 68 , 69 and Rh-catalyzed 70 electrochemical asymmetric syntheses. This observation revealed that the reduced Pd species instantly transfers an electron to 2a to generate intermediate E , which again accepts an electron from the cathode.…”
Section: Resultssupporting
confidence: 86%
“…Different from classical enolate chemistry, merging stereoselective Lewis acid catalysis with electrochemistry could provide anodic oxidation-triggered electrophilic keto radical based on a single electron transfer (SET) process, thus offering a unique opportunity to access modular structural complexity with predictable reactivity (Fig. 1A) (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed asymmetric electrosynthesis leading to intermolecular alkylation ( 36 ) and arylation ( 37 ) reactions. However, the electrochemical α-alkenylation of ketones has been sluggish to develop and thus is difficult for the development of chemo- and enantioselective carbon-carbon bond formation reactions with high efficiency ( 38 , 54 , 55 ). Furthermore, despite the immense synthetic potential of these reactions in organic synthesis, the discovery of divergent catalytic procedures from a common precursor rationally and predictably under electrolytic circumstances remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages render electrochemistry a sustainable, economical technique for chemical synthesis. However, rare examples have been realized in the eld of asymmetric electrosynthesis [49][50][51][52][53] . To our best knowledge, there is only one enantioselective report involving cobalt via electrochemistry, in which moderate enantioselectivity was reported with one single example (Fig.…”
Section: Introductionmentioning
confidence: 99%